Towards a new approach to analyzing the geographical scope of national research. An exploratory analysis at the country level - Miguel, Sandra Edith (2024)
This study aims to identify and compare the national scope of research at the country level, dealing with two groups of countries: Latin America and the Caribbean (LAC) and a group of countries at the forefront in developing mainstream science (WORLD). We wish to explore whether similar or different patterns arise between the two groups at the global and disciplinary level, becoming apparent in their proportion of research related to local perspectives or topics. It is found that Latin America and the Caribbean countries present a greater proportion of local production. The trend to publish national-oriented research is related to disciplinary fields. Even though English is the dominant language of publication, the lingua franca is more likely to appear in the national scope of research, especially for Latin America and the Caribbean countries but also in the rest of non-Anglophone countries. Some implications and limitations for further studies are described.